ANALISIS PERSEPSI PENERAPAN SISTEM INFORMASI PERPAJAKAN DAN KEPATUHAN WAJIB PAJAK PROFESI DOKTER - Nyoman Yudha Astriayu Widyari (Faculty of Economics and Business, Universitas Warmadewa, 2023)
This study aims to obtain empirical evidence regarding the perception of tax information systems and compliance by medical profession taxpayers using the TAM model and the DeLone & McLean model. The number of samples used was 45 samples selected by proportional random sampling. Data collection was carried out by distributing questionnaires. Data analysis techniques in this study used the SEM-PLS method. The results showed that perceived usefulness had a positive effect on tax compliance, while other variables, namely perceived ease of use, system usage, and system user satisfaction had no effect on tax compliance partially.